CD4 and LAG-3 from sharks to humans: related molecules with motifs for opposing functions - Takizawa, Fumio; Hashimoto, Keiichiro; Miyazawa, Ryuichiro; Ohta, Yuko; Veríssimo, Ana; Flajnik, Martin F.; Parra, David; Tokunaga, Kotaro; Suetake, Hiroaki; Sunyer, J. Oriol; Dijkstra, Johannes M. (Frontiers in Immunology, 2023)
CD4 and LAG-3 are related molecules that are receptors for MHC class II molecules. Their major functional differences are situated in their cytoplasmic tails, in which CD4 has an activation motif and LAG-3 an inhibitory motif. Here, we identify shark LAG-3 and show that a previously identified shark CD4-like gene has a genomic location, expression pattern, and motifs similar to CD4 in other vertebrates. In nurse shark (Ginglymostoma cirratum) and cloudy catshark (Scyliorhinus torazame), the highest CD4 expression was consistently found in the thymus whereas such was not the case for LAG-3. Throughout jawed vertebrates, the CD4 cytoplasmic tail possesses a Cx(C/H) motif for binding kinase LCK, and the LAG-3 cytoplasmic tail possesses (F/Y)xxL(D/E) including the previously determined FxxL inhibitory motif resembling an immunoreceptor tyrosine-based inhibition motif (ITIM). On the other hand, the acidic end of the mammalian LAG-3 cytoplasmic tail, which is believed to have an inhibitory function as well, was acquired later in evolution. The present study also identified CD4-1, CD4-2, and LAG-3 in the primitive ray-finned fishes bichirs, sturgeons, and gars, and experimentally determined these sequences for sterlet sturgeon (Acipenser ruthenus). Therefore, with CD4-1 and CD4-2 already known in teleosts (modern ray-finned fish), these two CD4 lineages have now been found within all major clades of ray-finned fish.Although different from each other, the cytoplasmic tails of ray-finned fish CD4-1 and chondrichthyan CD4 not only contain the Cx(C/H) motif but also an additional highly conserved motif which we expect to confer a function. Thus, although restricted to some species and gene copies, in evolution both CD4 and LAG-3 molecules appear to have acquired functional motifs besides their canonical Cx(C/H) and ITIM-like motifs, respectively. The presence of CD4 and LAG-3 molecules with seemingly opposing functions from the level of sharks, the oldest living vertebrates with a human-like adaptive immune system, underlines their importance for the jawed vertebrate immune system. It also emphasizes the general need of the immune system to always find a balance, leading to tradeoffs, between activating and inhibiting processes.